(untitled) (Research, Society and Development, 2020)
The aim of the study was to analyze the contents and approaches on cardiovascular patient safety in the education of nurses. It is a documentary study that used the method of Pimentel (2001), to analyze the guiding documents of education - pedagogical project, curricular matrix, menus and plans of disciplines - of a Nursing course at a public university in the interior of the Brazilian Northeast. The study was approved by the Research Ethics Committee of the State University of Ceará under protocol No. 923,537. The results of the analysis revealed a fragmented curriculum, with content and specific and indirect approaches on teaching patient safety in the cardiovascular context. The concept of patient safety was not identified in the analyzed documents, reinforcing the indirect approach to the theme. It is concluded that there is a need for greater curricular integration and reformulation of documents, in order to promote a clear and transversal approach to patient safety in nursing education.